Implementasi Sistem Pakar dalam Kalkulasi Bantuan Korban Bencana Alam dengan Metode Help Victims of Natural Disasters Calculation Using Expert System - Senna Hendrian; Muhammad Tri Habibie; Ade Kurnia Solihin; Umar Wirantasa; Wisdariah Wisdariah; Gerie Munggaran; V.H Valentino (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Handling natural disaster victims requires a fast, precise, and fair aid distribution process. In this context, expert systems can be utilized as a decision-making tool in determining the type and amount of aid that should be given to victims. This article develops a desktop-based expert system using the Java programming language, which is able to calculate the type of aid based on the condition of the victim, the level of damage, and the number of affected family members. The method used is a rule-based expert system with if-then logic. The results show that this system can assist field officers in accelerating the calculation and distribution of aid.